2014
DOI: 10.1073/pnas.1421438111
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Hypoxia-inducible factors are required for chemotherapy resistance of breast cancer stem cells

Abstract: Triple negative breast cancers (TNBCs) are defined by the lack of estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 expression, and are treated with cytotoxic chemotherapy such as paclitaxel or gemcitabine, with a durable response rate of less than 20%. TNBCs are enriched for the basal subtype gene expression profile and the presence of breast cancer stem cells, which are endowed with self-renewing and tumor-initiating properties and resistance to chemotherapy. Hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

20
404
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 445 publications
(433 citation statements)
references
References 58 publications
20
404
1
2
Order By: Relevance
“…Compared with other breast cancer subtypes, xCT and GCLM mRNA levels were significantly increased in basal breast cancers (Fig. S1C), in which hypoxia-inducible factor (HIF)-target gene expression is also increased (10). A detailed comparison of xCT and GCLM mRNA levels with those of CXCR3, L1CAM, BNIP3, PLOD1, P4HA1, P4HA2, VEGFA, SLC2A1, and CA9 mRNA, which are all HIFregulated gene products in TNBC cells, showed a significant correlation of xCT and GCLM expression with six of nine and eight of A B C D E F Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Compared with other breast cancer subtypes, xCT and GCLM mRNA levels were significantly increased in basal breast cancers (Fig. S1C), in which hypoxia-inducible factor (HIF)-target gene expression is also increased (10). A detailed comparison of xCT and GCLM mRNA levels with those of CXCR3, L1CAM, BNIP3, PLOD1, P4HA1, P4HA2, VEGFA, SLC2A1, and CA9 mRNA, which are all HIFregulated gene products in TNBC cells, showed a significant correlation of xCT and GCLM expression with six of nine and eight of A B C D E F Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We recently demonstrated that paclitaxel treatment increases the percentage of BCSCs in a HIF-dependent manner (10). xCT and GCLM expression in breast cancer cell lines is correlated with expression of CD44, an important BCSC marker (20,24).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In hypoxic breast cancer cells, HIFs activate the transcription of target genes that play important roles in tumor growth, angiogenesis, metabolic reprogramming, motility, invasion, metastasis, and resistance to chemotherapy (15,16). Recent studies have demonstrated that HIFs are required for the specification and/or maintenance of BCSCs in response to hypoxia (17)(18)(19)(20)(21) or chemotherapy (22,23), leading to direct or indirect transcriptional regulation of genes encoding the pluripotency factors NANOG, SOX2, and KLF4. In addition, HIF-1α is required for hypoxia-induced epithelial-mesenchymal transition (24), which is also linked to the BCSC phenotype (25).…”
mentioning
confidence: 99%